Jordanian Women’s Quest for Social Justice - Al-Braizat, Hind (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
This research paper aims to analyze the perspectives of a selection of Jordanian women between the ages of 20 and 50 on social justice and explore if ingrained gender discrimination prevents women from attaining equality in Jordan. It tries to pinpoint the factors that hinder or motivate women to pursue social justice in Jordan while identifying their views on the existing opportunities and barriers to achieving social justice. Results reveal that the profoundly ingrained dynamics of the Jordanian social structure—culture, socialization, and gender discrimination—play an integral part in preventing women from attaining social justice in Jordan. Moreover, the results show that collaboration between women and their political representatives in society is a must for fostering social justice in Jordan; it is not enough to rely only on providing a good education for women.